A rational-emotive stress management intervention for reducing job burnout and dysfunctional distress among special education teachers: An effect study. Issue 17 (April 2018) - Ugwoke, Samuel C.; Eseadi, Chiedu; Onuigbo, Liziana N.; Aye, Eucharia N.; Akaneme, Immaculata N.; Oboegbulem, Angie I.; Ezenwaji, Ifeyinwa O.; Nwobi, Anthonia U.; Nwaubani, Okechukwu O.; Ezegbe, Bernedeth N.; Ede, Moses O.; Orji, Chibueze T.; et al.
Abstract: Background: Job-related burnout and distress are adverse stress responses which affect individuals in their occupational environment. This study aimed at investigating the effect of a rational-emotive stress management program on job burnout and dysfunctional distress among special education teachers in Nigeria. Methods: A pretest–posttest randomized control group design was used. The participants in the study were 54 special education teachers. Data were collected using self-report questionnaires. Participants were allocated to either the treatment group (n = 28 [59.1%]) or the waitlist control group (n = 26 [48.1%]), respectively. A rational-emotive stress management manual was used to deliver the intervention. We statistically analyzed the data collected at three-time points with repeated-measures analysis of variance. Results: At baseline, the job-related burnout symptoms and distress scores of participants were high. However, an intention-to-treat analysis showed that the rational-emotive stress management intervention program was efficacious in reducing the levels of job-related burnout symptoms and dysfunctional distress among participants assigned to the treatment group, compared to a waitlisted group at post-treatment and follow-up meetings. Conclusion: Our study demonstrates the effectiveness of a rational-emotive stress management intervention in reducing the level of job-related burnout and distress in a sample of special education teachers in Nigeria. Occupational health counsellors and other clinicians with sufficient knowledge of rational-emotive behavior therapy framework are urged to employ this approach in assisting other employees in managing job burnout symptoms, and distress.